Response of tomato (Solanum lycopersicum) grafted on wild brinjal (Solanum torvum) rootstock for growth and yield - V, CHANDANSHIVE A; N, SONAVANE P; D, GAIKWAD S; KUMAR, VIKASH (The Indian Journal of Agricultural Sciences, 2023)
The present experiment was conducted to study the compatibility of different tomato (Solanum lycopersicum L.) varieties/hybrids grafted on wild brinjal (Solanum torvum Sw.) rootstock with an objective to study the effect of rootstock on growth, yield, graft success (%), crop duration and incidence of fusarium wilt in tomato. The study was carried out during rainy (kharif) season 2019 subsequently for 3 years and completed in winter (rabi) season 2022–23, which comprises 2 rootstocks, 3 scions in a factorial randomized block design (FRBD) with 9 treatments and 3 replications. The results were analyzed on the basis of 3 years pooled data with respect to growth and yield parameters. The grafting results showed significant increase in minimum number of days to 1st harvest (68.55), maximum fruit weight (81.04 g), number of fruit per plant (29.45), yield per plant (2.38 kg), yield per plot (85.68 kg) and yield per hectare (72.12 tonnes) over control. The graft combination of Phule Raja grafted on Solanum torvum showed maximum graft success (95.07%), less incidence of fusarium wilt (0.00%) with maximum crop duration of 235 days, i.e. an increase of 57 days compared to non-grafted. The benefit:cost (B:C) ratio analysis showed higher net monetary returns in grafted plants as compared to non-grafted plants. It is concluded that the grafting of Phule Raja on wild brinjal rootstock recommended for higher yield and less incidence of fusarium wilt.